Pengembangan desain kursi new normal untuk fasilitas duduk publik - Gracia Vita Kurniawan; Grace Mulyono; Taufan Rizqy (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2022)
Entering the new normal era, people need safe and comfortable public space seating facilities. Most of the existing public facilities are sufficient for the new normal era, but only a cross on the actual seat can still be used. Seeing these problems, the research was carried out with the aim of producing a new normal sitting facility with a modular and compact form, able to provide viruses, and provide users with protection from COVID-19. This study uses the Stanford D.School "Design Thinking" method which consists of 5 stages, namely; empathize, define, idealize, prototype, and test. Based on this method, the resulting product consists of 5 alternatives with the same function and product objectives. The concept presented is one that can provide virus spread and protect users from other user files, and uses a simple, modular style and product design.